Analisis Penerapan Sistem Informasi Akuntansi Penjualan Kredit Pada Pt Puji Surya Indah Cabang Madiun - Wamastri Eriati Mahdiyah; Mukti Prasaja; Gemelthree Ardiatus Subekti; Vaisal Amir (Politeknik Sawunggalih Aji, 2026)
This study aims to evaluate the credit sales accounting system at PT Puji Surya Indah Madiun by examining the alignment between the company’s current practices and the accounting system theories proposed by Mulyadi (2018) as well as the PIECES framework (Performance, Information, Economics, Control, Efficiency, Service). The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The results of the study indicate that the credit sales accounting system at the company does not fully comply with the principles of an accounting information system. Several weaknesses were identified, including the absence of a specific function responsible for handling credit, the lack of billing documents, and the absence of accounts receivable and warehouse cards that should be used as part of the accounting records. In addition, the product return process is still conducted manually and has not been properly documented within the system.